Seaport competition and strategic investment in accessibility - Basso, Leonardo J.; Wan, Yulai; Zhang, Anming (Congreso Chileno de Ingeniería de Transporte, 2013)
We investigate strategic investment decisions of local governments on inland transportation infrastructure in the context of seaport competition. We consider two seaports with their respective catchment areas and a common hinterland for which seaports compete. The two seaports and the common hinterland belong to three independent local governments, each determining the level of investment for its own inland transportation system. We find: (i) increasing investment in the hinterland lowers charges at both ports; and (ii) increasing investment in a port’s catchment area will cause severer reduction in charge at its port than at the rival port. We also examine the non-cooperative optimal investment decisions and equilibrium investment levels under various coalitions.